The Effect of Workload, Emotional Intelligence, and Work Communication on Employee Performance at the Secretariat of The Directorate General of Health Personnel of the Republic of Indonesia - Astuti, Widi; Zurnali, Cut (Journal of Economics and Business (JECOMBI), 2025)
Employee performance plays a crucial role in supporting the effectiveness of government institutions, especially in the public health sector. Recognizing the importance of maintaining high employee performance, this study aims to examine the influence of workload, emotional intelligence, and work communication on employee performance at the Secretariat of the Directorate General of Health Personnel of the Republic of Indonesia. Employing a quantitative method with saturated sampling involving 125 employees, data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS software. The results show that workload (β = 0.220, p = 0.017), emotional intelligence (β = 0.230, p = 0.020), and work communication (β = 0.251, p = 0.010) each have a positive and significant effect on employee performance. Furthermore, the model explains 34.4% of the variation in performance (R² = 0.344). These findings suggest that managing workload balance, strengthening emotional intelligence, and enhancing communication systems are strategic approaches to improving employee performance. This research provides practical insights for public sector human resource development and highlights the need for future studies to explore additional influencing factors such as leadership style, motivation, and organizational culture.